2007
DOI: 10.1007/s00213-006-0633-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of olanzapine, risperidone and haloperidol on sleep after a single oral morning dose in healthy volunteers

Abstract: Objectives To compare the effects of typical and atypical antipsychotic drugs on sleep activity and subjective sleep quality. Design Randomised, double-blind, placebo-controlled, four-period cross-over, clinical trial was used to evaluate the effects of active treatments on objective and subjective sleep variables. Setting Sleep laboratory evaluation. Participants Twenty healthy young volunteers, both sexes. Interventions Single oral morning administrations of olanzapine 5 mg, risperidone 1 mg, haloperidol 3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
42
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 23 publications
8
42
0
3
Order By: Relevance
“…This discrepancy might be a result of its more complex pharmacological action [48]. Haloperidol, however, has been shown to have a sleep-promoting effect, concordant with our results [24]. Considering the sleep-disturbing effect, clozapine appears to be more hazardous.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This discrepancy might be a result of its more complex pharmacological action [48]. Haloperidol, however, has been shown to have a sleep-promoting effect, concordant with our results [24]. Considering the sleep-disturbing effect, clozapine appears to be more hazardous.…”
Section: Discussionsupporting
confidence: 81%
“…Since the acetylcholine and monoamines are all known to be involved in the regulation of sleep, these drugs are expected to modify the sleep-wake cycle [22,23,24]. Along the sleep-wake cycle, sympathetic and parasympathetic activity fluctuates cyclically, with higher vagal activity during quiet sleep (QS) and higher sympathetic activity during wakefulness and paradoxical sleep (PS) [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that morning doses of olanzapine produce a more striking SWS enhancement than evening administrations [29] . Significant increases in SWS were also elicited in our study [15] . However, since the main EEG biomarker of sleep homeostasis is the exponential decline of SWA but not the SWS [2] , the time course of this measure was calculated.…”
Section: Discussionsupporting
confidence: 55%
“…In order to assess this objective, data coming from the study of Giménez et al [15] were used. In this study significant hypnotic effects of olanzapine oral morning administration were observed.…”
Section: Introductionmentioning
confidence: 99%
“…The latter have made large investments in this research field, trying to develop safer and more effective drugs able to regulate the sleep-wake alternation. But it is of particular importance that the therapeutic interventions also maintain the physiological sleep architecture (2,3), which is a physiologically relevant description of the sequence of sleep stages (REM, slow-wave sleep, awake, etc.) coming one after the other during nighttime.…”
Section: Introductionmentioning
confidence: 99%